1984
DOI: 10.1002/neu.480150504
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the chick's magnesium‐sensitive retinal spreading depression

Abstract: Spreading depression (SD) in the chick retina is completely suppressed by 10 mM MgCl2 in the bathing solution (Mg-sensitive SD). However, after increasing the KCl concentration in the Mg solution to values between 10 and 20 mM the retina can again exhibit SDs (Mg-insensitive SD). It has been postulated that the Mg-sensitive SD is a glutamatergic phenomenon. This is supported by the effect of four gl(utamate)-antagonists--L-proline, glutamic acid diethyl ester (GDEE), D-alpha-aminoadipate (D-AA), and 2-amino-4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…pO 2 of 140 mmHg (corresponding to ∼20% oxygen) was maintained in the gas phase directly above the retinas. Under our experimental conditions, 6 mM MgCl 2 (n = 20) completely suppressed SD, as reported (18).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…pO 2 of 140 mmHg (corresponding to ∼20% oxygen) was maintained in the gas phase directly above the retinas. Under our experimental conditions, 6 mM MgCl 2 (n = 20) completely suppressed SD, as reported (18).…”
Section: Resultssupporting
confidence: 85%
“…TTX, which does not block SD (8), did not prevent SD-induced cell death (n = 8). Both MgCl 2 and halothane blocked initiation of SD waves (18,21) and prevented development of punctate lesions and lesion expansion (Figs. 3 B and C and 4B), as well as activation of caspase 3 ( Fig.…”
Section: Mechanisms Whereby Hypoglycemia Leads To Reentrant Spiral Sdmentioning
confidence: 94%
“…In comparison to control subjects, the levels of magnesium (Mg), measured with 31 pNMR were found significantly lower in the brain of migraine patients, particularly during migraine attacks [17]. Mg is the unique compound known to block glutamate-dependent SD [18]. Lamotrigine is an antiepileptic drug acting by blocking voltage-sensitive channels leading to an inhibition of glutamate release [19].…”
Section: Glutamate and Auramentioning
confidence: 98%
“…It has been demonstrated that CSD is completely blocked by competitive and noncompetitive NMDA antagonists (Van Harreveld, 1984;Mody et aI., 1987;Goroleva et aI., 1987;Hansen et aI., 1988;Lauritzen et al, 1988;Marrannes et al, 1988). Therefore, if hypoglycemic depolarization and CSD were triggered by the same mechanism, we would expect some degree of blockage of the persistent depolarization in severe hypoglycemia in response to NMDA antagonism.…”
Section: Discussionmentioning
confidence: 94%